On the accuracy of cell-attached current-clamp recordings from cortical neurons - Vazetdinova, Alina; Valiullina-Rakhmatullina, Fliza; Rozov, Andrei; Evstifeev, Alexander; Khazipov, Roustem; Nasretdinov, Azat (Frontiers in Molecular Neuroscience, 2022)
Cell-attached current-clamp (CA/CC) recordings have been proposed to measure resting membrane potential and synaptic/agonist responses in neurons without disrupting the cell membrane, thus avoiding the intracellular dialysis that occurs in conventional whole-cell recordings (WC). However, the accuracy of CA/CC recordings in neurons has not been directly assessed. Here, we used concomitant CA and WC current clamp recordings from cortical neurons in brain slices. Resting membrane potential values and slow voltage shifts showed variability and were typically attenuated during CA/CC recordings by 10–20% relative to WC values. Fast signals were slowed down and their amplitude was greatly reduced: synaptic potentials by nearly 2-fold, and action potentials by nearly 10-fold in CA/CC mode compared to WC. The polarity of GABAergic postsynaptic responses in CA/CC mode matched the responses in WC, and depolarising GABAergic potentials were predominantly observed during CA/CC recordings of intact neonatal CA3 hippocampal pyramidal neurons. Similarly, CA/CC recordings reliably detected neuronal depolarization and excitation during network-induced giant depolarizing potentials in the neonatal CA3 hippocampus, and revealed variable changes, from depolarization to hyperpolarization, in CA1 pyramidal cells during sharp wave ripples in the adult hippocampus. Thus, CA/CC recordings are suitable for assessing membrane potential but signal distortion, probably caused by leakage via the seal contact and RC filtering should be considered.